2019
DOI: 10.1177/0003489418823794
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Sialendoscopy for Recurrent Salivary Gland Swelling: Workup, Findings, and Outcomes

Abstract: Introduction: Recurrent salivary gland swelling of the parotid and submandibular glands results in painful swelling in the pediatric population. There is no defined algorithm for workup and treatment of these disorders, resulting in wide heterogeneity and in some cases overuse of computed tomography (CT) imaging. Sialendoscopy (SE) is an interventional option for recurrent swelling of both glands; however, its effectiveness in the pediatric population is still being determined. Objectives: To assess preoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…Some authors raise questions whether to attribute positive outcomes in JRP to sialendoscopy or to the natural history of the disease based on the higher age of children with better clinical response. 22 However this was not the case in our study as such correlation was not found.…”
Section: Discussioncontrasting
confidence: 70%
“…Some authors raise questions whether to attribute positive outcomes in JRP to sialendoscopy or to the natural history of the disease based on the higher age of children with better clinical response. 22 However this was not the case in our study as such correlation was not found.…”
Section: Discussioncontrasting
confidence: 70%
“…Amoxicillin-clavulanic. Cephalosporin N/A Borner et al [ 14 ] Fibrous, stenosis Methylprednisolone LA /GA N/A N/A Velasquez et al [ 27 ] Fibrinous debris, duct stenosis Triancinolona GA N/A N/A Capaccio et al [ 35 ] Mucous plugs, stenosis, debris, pale duct SS + dexamethasone Sedation Amoxicillin Swelling (1 case) and pain (N/A) Iordanis et al [ 21 ] N/A SS + prednisone GA Amoxi-clavulanate (1 day preOP) N/A Kanerva et al [ 15 ] N/A SS ± hydrocortisone GA/LA None Swelling (1 case) Gellrich et al [ 16 ] N/A SS + prednisone N/A N/A N/A Nation et al [ 17 ] Sludg, stenosis SS ± steroids (solumedrol, hydrocortisone, triamcinolone, decadron) GA N/A None Berlucchi et al [ 28 ] Mucous plugs, stenosis, debris, pale duct SS + hydrocortisone GA Yes (postOP) None Faizal et al [ …”
Section: Resultsmentioning
confidence: 99%
“…The same number of episodes but in a 12-month period was the criterion for sialoendoscopy, which was applied in 213 patients [ 7 , 9 , 11 , 18 , 27 30 ]. In 11 studies in our review, the presence of two or more episodes of parotid swelling was reported as a criterion, but without specifying the time of presentation [ 1 , 14 , 15 , 17 , 19 , 20 , 31 35 ]. Two authors, Gellrich et al [ 16 ] and Singh et al [ 36 ] describe, in their series, the indication for the technique included patients who presented a minimum of five or six episodes of swelling in 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, sialendoscopy may be a useful diagnostic tool for the assessment of a specific obstructive etiology for sialadenitis and thus allows for the correct diagnosis of JRP. However, intraoperative findings of a specific obstructive etiology, as stones or ductal stenosis are rare [ 18 ]. Furthermore, the effect of the mechanical manipulation by introducing and advancing the endoscope remains unknown.…”
Section: Discussionmentioning
confidence: 99%